Glucocorticoid-Induced TNF Receptor Family-Related Protein Ligand is Requisite for Optimal Functioning of Regulatory CD4+ T Cells - Liao, Gongxian; O’Keeffe, Michael S.; Wang, Guoxing; van Driel, Boaz; de Waal Malefyt, Rene; Reinecker, Hans-Christian; Herzog, Roland W.; Terhorst, Cox (Frontiers in Immunology, 2014)
Glucocorticoid-Induced Tumor necrosis factor Receptor family-related protein (GITR, TNFRSF18, CD357) is constitutively expressed on regulatory T cells (Tregs) and is inducible on effector T cells (Teffs). In this report, we examine the role of GITR-Ligand (GITR-L), which is expressed by antigen presenting cells, on the development and expansion of Tregs. We found that GITR-L is dispensable for the development of naturally occurring FoxP3+ Treg cells in the thymus. However, the expansion of Treg in GITR-L-/- mice is impaired after injection of the dendritic cells (DCs) inducing factor Flt3 ligand. Furthermore, DCs from the liver of GITR-L-/- mice were less efficient in inducing proliferation of antigen-specific Treg cells in vitro than the same cells from WT littermates. Upon gene transfer of ovalbumin into hepatocytes of GITR-L-/- FoxP3(GFP) reporter mice using adeno-associated virus (AAV8-OVA) the number of antigen-specific Treg in liver and spleen is reduced. The reduced number of Tregs resulted in an increase in the number of ovalbumin specific CD8+ T effector cells. This is highly significant because proliferation of antigen specific CD8+ cells itself is dependent on the presence of GITR-L, as shown by in vitro experiments and by adoptive transfers into GITR-L-/-Rag-/- and Rag-/- mice that had received AAV8-OVA. Surprisingly, administering αCD3 significantly reduced the numbers of FoxP3+ Treg cells in the liver and spleen of GITR-L-/- but not WT mice. Because soluble Fc-GITR-L partially rescues αCD3 induced in vitro depletion of the CD103+ subset of FoxP3+CD4+ Treg cells, we conclude that expression of GITR-L by antigen presenting cells is requisite for optimal Treg-mediated regulation of immune responses including those in response during gene transfer.